Suitability Analysis of Beach Ecotics in Gua Manik Beach and Benteng Beach of Portuges, Jepara District - Rojana, Ahmad Rifqi Faqih; Muhsoni, Firman Farid (Jurnal Perikanan dan Kelautan, 2022)
The development of ecotourism based on the preservation of natural resources is very important so that its sustainability does not damage the environment. Banyumanis Village, Donorojo Subdistrict, Jepara Regency has tours of Gua Manik Beach and Portuguese Fort Beach which were developed for coastal ecotourism. The purpose of this study is to analyze the value of the Tourism Suitability Index, Area Supporting Capacity, and Utilization Support Capacity in that location. The method used is to calculate IKW, DDK and DDP . The research results of the Tourism Suitability Index Pantai Gua Manik 85.71% (appropriate) and Fort Portuguese Beach 76.19% (appropriate). The value of Area Supporting Capacity at Gua Manik beach is 1185 people/day and Fort Portuguese beach is 240 people/day. The Utilization Support Capacity value for Gua Manik beach is 118 people/day and Fort Portuguese beach is 24 people/day